Al-Manhaj fῑ Ta’lῑmi Al-lugah Al-‘arabiyyah ‘alᾱ Ḍau’ An-naẓariyyah Al-Binᾱiyyah - sholeha, Nur hanifatus; nisa, fathimah kamilatun (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2020)
Modern linguistic theories have developed based on situations and conditions produced by humans, depending on various kinds of goals to be achieved. Constructivistic theory is one of the theories of modern linguistics which is built on the awareness that the true meaning of learning is not only enough to build students' habits of listening to explanations from the teacher even though learning is carried out by the method of students memorizing and repeating lessons in front of the teacher. This theory adheres to the belief that a student is able to construct and explore information and knowledge that is within him by harmonizing the influence of the environment around him, including society and language. This theory is a form of rejection of behavioristic learning theory which emphasizes the need for students to stimulate the stimulus provided by their environment, where students do not get the opportunity to explore competence, knowledge, or experience freely. Constructivism theory believes that each individual has their own methods and characteristics in understanding information which does not rule out that it will be different from the teacher and the learning process imposed by the teacher by providing knowledge monotonously to students both through reinforcement and repetition in constructivism theory can be contradictory with what is interwoven in students' cognitive. In other words, students are active subjects who build cognitive structures with their environmental interactions. The purpose of this paper is to determine the concept of constructivist theory, the history of its development, characteristics, goals, advantages, and concept maps.